2015
DOI: 10.1038/mi.2014.121
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin causes IgA and IgG2b isotype switching through betaglycan binding and activation of canonical TGF-β signaling

Abstract: Lactoferrin (LF), a pleiotropic iron-binding glycoprotein, is known to modulate the humoral immune response. However, its exact role in Ig synthesis has yet to be elucidated. In this study, we investigated the effect of LF on Ig production by mouse B cells and its underlying mechanisms. LF, like transforming growth factor (TGF)-β1, stimulated B cells to produce IgA and IgG2b, while downregulating other isotypes. Using limiting dilution analysis, LF was shown to increase the frequency of IgA-secreting B-cell cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 51 publications
3
39
1
Order By: Relevance
“…13 Additionally, we recently reported that LF enhanced IgA CSR by binding to TbRIII (betaglycan) and activating canonical TGF-b signaling. 19 The present study extends these findings. Thus, similar to our findings with TGF-b1 plus RA, LF and RA synergized to increase IgA CSR.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…13 Additionally, we recently reported that LF enhanced IgA CSR by binding to TbRIII (betaglycan) and activating canonical TGF-b signaling. 19 The present study extends these findings. Thus, similar to our findings with TGF-b1 plus RA, LF and RA synergized to increase IgA CSR.…”
Section: Discussionsupporting
confidence: 78%
“…This LF/RA combination effect was expected to some extent because LF functions through canonical TGF-b signaling as noted above. 19 Nevertheless, the mechanisms underlying IgA CSR caused by the combination of TGF-b1/RA and LF/RA will not be entirely identical because the role played by RA is believed to differ from the TGF-b1/RA and LF/RA combinations. Previously, we observed that RA could directly increase IgA CSR on its own and that the RA signal transduced through RAR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations